Epidemiology, Pathology, and Diagnosis of Urinary Schistosomiasis: An In-Depth Review - A. T. Ogundipe; S. M. Gamde; B. D. Oyedun; A. G. Nnenna; K. I. Bali; B. Abigail; E. A. Inyang; C. Biya; H. I. Ogah; S. M. Udo; A. V. Ikechukwu; E. A. Yetunde (Journal of Applied Sciences and Environmental Management)
Urinary schistosomiasis is a formidable public health problem, particularly among children bearing the most burden of the disease as they are more liable to play in infected water with women also at higher risk due to daily chores that involve water contact, such as washing clothes and fetching water, other high-risk groups are farmers, fishermen, and people using shistosome infected water. Hence the objective of this paper is to provide an in-depth review of the epidemiology, pathology, and diagnosis of urinary schistosomiasis through a rigorous search on Scopus, Pub Med, Google Scholar, and Research Gate an overview on Urinary schistosomiasis and crucial insights on targeted interventions tailored to meet the needs of affected people with limited access to healthcare services. Based on our knowledge, eliminating schistosomiasis in poor countries with constrained health services would be a difficult task. In this context, addressing the underscored issues will escalate the journey toward the goal of schistosomiasis elimination.